Classifying divided cities: the need for geopolitical perspective? - Zorko, M.; Novak, N. (Sociologija i prostor, 2019)
Divided cities are common phenomena in contemporary world. Each case is driven out of a different set of factors and consists of different manifestations of divisions. This paper seeks to identify the categorization of divisions and offer the criteria that should be considered when researching the phenomenon of divided cities. The geopolitical perspective may serve as a tool for overcoming the confusion in different sets of classifications. The authors suggest four sets of criteria within which divided cities have to be considered when rethinking a geopolitical perspective on this issue. Divided cities are an empirical state of fact and appear across the Globe. Moreover, most of world cities are somehow divided, but cannot be called divided cities in geopolitical terms. This paper shows the differences in divisions taking into account geographical, political, identity and power relations bringing them into a geopolitical set of related criteria.